Error-correction capability of Reed-Muller codes - Dib, Stéphanie; Rodier, François (Arithmetic, Geometry, Cryptography and Coding Theory)
We present an asymptotic limit between correctable and uncorrectable errors on the Reed-Muller codes of any order and give its value. This limit is theoretical and does not depend on any decoding algorithm.